The Solution.
The given system of equations is
![\begin{gathered} y=x^2-6\ldots eqn(1) \\ y=-2x+9\ldots eqn(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8jyefdp2huap8t004onuplc51h4t1hjk26.png)
Equating both equations, we get
![x^2-6=-2x+9](https://img.qammunity.org/2023/formulas/mathematics/college/m099rd5ls251dt2zsdt5lr50oizs9dwo7x.png)
![\begin{gathered} x^2+2x-6-9=0 \\ x^2+2x-15=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/42qf8fi5hcm4j7q1ut39swat52wl7nyks8.png)
Solving the equation quadratically by Factorization Method.
We use 2x and - 5x to replace - 2x. we get
![x^2-3x+5x-15=0](https://img.qammunity.org/2023/formulas/mathematics/college/y2nay558ruejlt7t992v2lpz6jiiepr2k5.png)
Factorizing, we get
![x(x-3)+5(x-3)=0_{}](https://img.qammunity.org/2023/formulas/mathematics/college/zmb599sjlcnb41egj5llglw9qv1aljgsof.png)
![\begin{gathered} (x+5)(x-3)=0 \\ x+5=0\text{ or x-3=0} \\ x=-5\text{ or x=3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a4kaz7av6cu1mvr48ik7ebw8emrgf9m67v.png)
Substituting -5 for x, in eqn(2), we get
![\begin{gathered} y=-2x+9 \\ y=-2(-5)+9 \\ y=10+9=19 \\ (x=-5,y=19)\text{ or (-5,19)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ak4ivgi7o0visuqvo092949eoc2vlsu9yg.png)
Substituting 3 for x, in eqn(2), we get
![\begin{gathered} y=-2(3)+9 \\ y=-6+9=3 \\ (x=3,y=3)\text{ or (3,3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2vyc6hpxwjgtk6uoba740srjr71wqsoo89.png)
Hence, the correct answers are (-5,19) or (3,3)